2009
DOI: 10.1130/g25147a.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for focused magmatic accretion at segment centers from lateral dike injections captured beneath the Red Sea rift in Afar

Abstract: Continental breakup occurs through repeated episodes of mechanical stretching and dike injection within discrete, narrow rift segments. However, the time and length scales of the dike intrusions, along with the source regions of melt within continental and oceanic rifts, are poorly constrained. We present measurements of spatial and temporal variability in deformation from the currently active 60-km-long Dabbahu segment of the Red Sea rift in Afar, using satellite radar, global positioning system, and seismici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
164
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(178 citation statements)
references
References 28 publications
13
164
1
Order By: Relevance
“…Along the rift axis the graben is disrupted by the volcanic topography associated with the Ado Ale Volcanic complex (AVC), a series of faulted silicic lavas flows/domes on the rift flanks and a basaltic volcano at the rift axis with a summit crater, and at its northern end the Dabbahu volcano, which has been active since at least B80 ka (refs 25 and (S. Medynski personal communication)). Seismic [11][12][13] and geodetic [14][15][16][17] observations of the recent dyking events are consistent with a magma source located in the rift centre below the AVC. This central volcanic region also marks a division in the width and morphology of the axial graben and rift flanks between the southern (graben B8 km wide, scarps B100 m high, significant flank topography) and northern (graben B4 km wide, scarps B30-50 m high, smooth flank profile) sectors (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Along the rift axis the graben is disrupted by the volcanic topography associated with the Ado Ale Volcanic complex (AVC), a series of faulted silicic lavas flows/domes on the rift flanks and a basaltic volcano at the rift axis with a summit crater, and at its northern end the Dabbahu volcano, which has been active since at least B80 ka (refs 25 and (S. Medynski personal communication)). Seismic [11][12][13] and geodetic [14][15][16][17] observations of the recent dyking events are consistent with a magma source located in the rift centre below the AVC. This central volcanic region also marks a division in the width and morphology of the axial graben and rift flanks between the southern (graben B8 km wide, scarps B100 m high, significant flank topography) and northern (graben B4 km wide, scarps B30-50 m high, smooth flank profile) sectors (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Observations of the multiple (B14) dyke intrusions 3,[11][12][13][14][15][16][17] and fissure eruptions 18 during this active phase have shown that in the upper part of the crust, the delivery of melts to the DMH rift zone is currently strongly focused along the rift axis. The overall scale and morphology of this B15 Â 60 km magmatic segment is similar to a slow (B20 mm per year) spreading mid-ocean-ridge segment 6 , such as those found along the Mid-Atlantic ridge 19,20 , and the recent episodic rifting activity is similar to that previously observed in Iceland 4,21 .…”
mentioning
confidence: 99%
“…These dykes are typically 1-3 m thick, 10-15 km long, and have a cumulative volume of 1 km 3 (Grandin et al, 2010;Hamling et al, 2009). Seismicity data show that they were all fed from the AVC and propagated at rates of 0.2-0.6 m/s Grandin et al, 2011;Keir et al, 2009b). As was the case during the September 2005 intrusion, dike-induced faulting accompanied intrusion but made a relatively minor contribution to the total deformation.…”
Section: The 2005-2011 Dabbahu-manda-harraro Rifting Episodementioning
confidence: 95%
“…This has often been observed during dike intrusions, for instance in Afar in 2006 [Grandin et al, 2009;Keir et al, 2009], at the volcanic island of Izu in 2000 [Nishimura et al, 2001] or during the 2007 Natron faulting and diking event [Baer et al, 2008;Calais et al, 2008;Biggs et al, 2009]. Large earthquakes, such as the 3 February 2002 5.9 M w Bukavu event [d 'Oreye et al, 2011], or the October 24, 2002 6.2 M w south Lake Kivu event ( Figure S8 in the auxiliary material), might remain undetected by interferometry if they were to occur beneath Lake Kivu or in areas of low coherence.…”
Section: Eruption Modelmentioning
confidence: 99%
“…Therefore, compared to better-studied rifting events, such as the Manda-Hararo 2005-2010 diking events [Keir et al, 2009;Grandin et al, 2010] or the Puu' Oo 1983 eruption [Rubin et al, 1998], it is not possible to detect if the deep dike was fed by a mid-segment reservoir.…”
Section: Eruption Modelmentioning
confidence: 99%